Individual patient data meta-analysis of neoadjuvant chemotherapy followed by surgery versus upfront surgery for carcinoma of the oesophagus or the gastro-oesophageal junction. (November 2021) - Faron, Matthieu; Cheugoua-Zanetsie, Armel Maurice; Thirion, Pierre; Nankivell, Matthew; Winter, Kathryn; Cunningham, David; Van der Gaast, Ate; Law, Simon; Langley, Ruth; de Vathaire, Florent; Valmasoni, Michele; Mauer, Muriel; et al.
Abstract: Introduction: Which neoadjuvant treatment for locally advanced thoracic oesophagus (TE) or gastro-oesophageal junction carcinoma is best remains an open question. Randomised controlled trials variously accrued patients with adenocarcinoma and squamous cell carcinoma, making strong conclusions hard to obtain. The primary objective of this individual participant data meta-analysis was to investigate the effect of neoadjuvant chemotherapy on overall survival (OS). Patients and methods: Eligible trials should have closed to accrual before 2016 and compared neoadjuvant chemotherapy and surgery (CS) to surgery alone. All relevant published and unpublished trials were identified via searches of electronic databases, conference proceedings and clinical trial registers. The main end-point was OS. Investigators were contacted to obtain the individual patient data, which was recorded, harmonised and checked. A random-effects Cox model, stratified by trial, was used for meta-analysis and subgroup analyses were preplanned. Results: 16 trials were identified as eligible. Individual patient data were obtained from 12 trial and 2478 patients. CS was associated with an improved OS versus surgery, hazard ratio (HR) = 0.83 [0.72–0.96], p < 0.0001, translating to an absolute benefit of 5.7% at 5-years from 16.8% to 22.5%. Treatment effects did not vary substantially between adenocarcinoma (HR = 0.73 [0.62–0.87]) and squamous cell carcinoma (HR = 0.91 [0.76–1.08], interaction p = 0.26). A somewhat more pronounced effect was observed in gastro-oesophageal junction (HR = 0.68 [0.50–0.93]) versus TE (HR = 0.87 [0.75–1.00], interaction p = 0.07). CS was also associated with a greater disease-free survival (HR = 0.74 [0.64–0.85], p < 0.001). Conclusions: Neoadjuvant chemotherapy conferred a better OS than surgery alone and should be considered in all anatomical location and histological subtypes. Highlights: Preoperative chemotherapy leads to better overall survival. Disease-free survival was better too. No differences were seen between squamous cell carcinoma and adenocarcinoma. Greater effect for tumour located in the gastro-oesophageal junction. No differences in postoperative morbidity or mortality.